Adiponectin and highly sensitive C-reactive protein levels in obese children aged 9 to 15 years - Frecilia Regina; Kristellina Tirtamulia; Sarah Maria Warouw (Indonesian Pediatric Society, 2011)
Background Childhood obesity is a widespread and growing problem associated with health problems such as metabolic syndrome, diabetes mellitus and cardiovascular disease. A lowô€—grade chronic inflammatory state, reflected by decreased adiponectin and increased highly sensitive Cô€—reactive Â protein (hsCRP) levels, may play a role in metabolic syndrome associated with obesity.Objective To assess and compare adiponectin and hsCRP levels in obese and nonnal weight children.Methods We conducted a cross-sectional, caseô€—controlled study in Manado from May to July 2010. Subjects were selected from obese, but otherwise healthy children aged 9-15 years. Control subjects were schoolmates 'With normal body mass index (BMI). We perfonned physical examinations, measured blood pressure, weight and height, and calculated BMI for all subjects. After an overnight fast, all subjects were tested for fasting blood glucose, adiponectin and hsCRP levels.Results The mean adiponectin level in the obese group was 3.6 Î¼g/mL (SD 1.43), lower than that of the normoweight group, 4.8 Î¼g/mL (SD 1.67) (P<0.0001). The mean hsCRP level in the obese group was 3.3 mg/L (SD 3.62) while that of the normoweight group was 0.8 mg/L (SD 1.39) (P<0.0001). There was no inverse correlation between adiponectin and hsCRP levels in obese group (r= 0.048; P= 0.362).Conclusions Lower adiponectin and higher hsCRP levels in the obese group is consistent 'With a low-grade chronic inflammatory state. Other factors that influence adiponecrin and hsCRP production or inflammatory pathways of other adipokines need further evaluation. Early intervention is needed to reduce body weight in obese children.